The importance of Naples prognostic score in predicting long-term mortality in heart failure patients - Sidar Şiyar Aydın; Selim Aydemir; Murat Özmen; Emrah Aksakal; İbrahim Saraç; Faruk Aydınyılmaz; Onur Altınkaya; Oğuzhan Birdal; İbrahim Halil Tanboğa (Annals of Medicine)
Background Heart failure (HF) remains a significant health problem despite advances in diagnosis and treatment options. Malnutrition and increased inflammation predict poor disease prognosis. The parameters of the Naples prognostic score (NPS) include albumin, total cholesterol, neutrophil-lymphocyte ratio (NLR), and lymphocyte-monocyte ratio (LMR). We aimed to assess the potential of NPS as a predictor of long-term mortality in patients with HF.Methods A total of 1728 patients with HF who applied to our center between 2018 and 2022 were included in this study. The NPS was computed and the patients were divided into three groups according to their NPS values as follows: NPS = 0 (Group 1), NPS = 1–2 (Group 2), and NPS = 3–4 (Group 3). We also evaluated the association between NPS value and HF mortality.Results The patients were followed for a mean follow-up duration of 30 months. The mortality rate was 8.3% (145 patients). We carried out Model-1 and -2 Cox regression analyses to identify long-term mortality determinants. Model-2 was constructed by adding NPS to Model-1. NPS was significantly associated with HF mortality (Hazard Ratio: 2.194, 95% Confidence Interval: 1.176–4.091, p = 0.014). According to the Kaplan-Meier plot and log-rank analyses, there was a statistically significant difference in the long-term mortality of patients with HF and their NPS values for the entire cohort.Conclusion Based on our findings, NPS showed promise as an independent predictor of long-term mortality in individuals with HF.